Modern Religious Slavery in Nigeria: The Christian Perspective - Emmanuel Williams Udoh (Universitas Negeri Makassar, 2021)
Gandhi's concept of nonviolence has a humanistic approach. He tried to change the very character of every Indian in the society where he lived. He said that man is basically a violent being, but gradually he can become non-violent if he desires. He recognizes that man is a conditional being and as such subject to the determination of the physical world. The ultimate end in man's life for Gandhi is realizing the Absolute. Pertinent to note that, Gandhi had spent quite some time in his tutelage in Southern Africa where his experiences impelled him to adopt non-violence as the only paradigm to overcome oppression and domination in his country India. British oppression and inhumanity were so severe and intensive that Gandhi was cautious about the use of violence, alternatively, he adopted non-violence to be the only imperative paradigm to dislodge the domination and inhumane treatment of the British against the Indians in South Africa. In this respect, I recommend Gandhi's non-violence principles as a fundamental paradigm towards peace in Africa. Peace in Africa is imperative for human and societal development especially as one sees Africa grappling with instabilities, insurgencies, terrorism, xenophobia, political upheavals, nepotism and gender agitations. In this article, I recognize Gandhi’s postulations on non-violence as an initiative which if adopted and its dictates are adhered to, could enhance peace in Africa.